2020
DOI: 10.1002/pa.2370
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of pay‐on‐delivery mode of payment and social media constructs as predictors of online purchase intentions

Abstract: The present research study has examined social media constructs, pay‐on‐delivery (POD) mode of payment, and its relationship with purchase intentions while making online purchases. The data were collected through an online as well as an offline survey from respondents in North Indian states. An online survey questionnaire link was shared on different social media platforms and social networking sites. A total of 385 responses were received, of which 354 responses were considered for the study. Results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Digalwar and Giridhar (28) emphasized upon lack of community cognizance, negligible assurance by government, and financial constraints as vital impediments to the development of car market in India. Limited and deficient rechargeable infrastructure pose another challenge in adoption of an eVehicle in India (29,41,42,43). In a white paper entitled, "EV-Ready India Part I: Value Chain Analysis of State EV policies" compiled by "World Economic Forum (30) in a study in collaboration with Ola Mobility Institute suggested a prerequisite to frame suitable promotional policies along with financial support frameworks.…”
Section: Barriers Across Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Digalwar and Giridhar (28) emphasized upon lack of community cognizance, negligible assurance by government, and financial constraints as vital impediments to the development of car market in India. Limited and deficient rechargeable infrastructure pose another challenge in adoption of an eVehicle in India (29,41,42,43). In a white paper entitled, "EV-Ready India Part I: Value Chain Analysis of State EV policies" compiled by "World Economic Forum (30) in a study in collaboration with Ola Mobility Institute suggested a prerequisite to frame suitable promotional policies along with financial support frameworks.…”
Section: Barriers Across Indiamentioning
confidence: 99%
“…Though strongly recommended worldwide for reducing greenhouse gas emissions, eVehicle adoption is very slow in-spite due to presence of bottlenecks which prohibit its entry. Existing studies related to barriers though cover multidimensional constructs, but extensive research to identify and validate impediments is still much needed (40)(41)(42)(43)47). This research study builds up a conceptual base and improves our understanding of different barriers and their dependence on policy and decision making.…”
Section: Implications Of the Studymentioning
confidence: 99%